Implikasi Yuridis Keputusan Mahkamah Konstitusi No. 69/PUUXIII/2015 Tentang Perjanjian Perkawinan Terhadap Harta Bersama Bagi Pernikahan Campuran - Badrut Tamam (Indonesian Journal of Islamic Law, 2021)
ABSTRACT Mixed marriages that occur in Indonesia, the perpetrators often do not pay attention to and know the steps of the rules before making a mixed marriage, especially those concerning the joint assets acquired throughout the marriage. someone who does mixed marriages cannot freely buy land rights in Indonesia because his spouse is a foreign national. This is due to the limitation of land ownership rights stipulated in Indonesian land law article 1 jo Article 21 of Law Number 5 Year 1960 which is based on nationality, in fact it has a socialization that is by conducting an Agreement on marriage, but lack of knowledge of mixed marriages so that it is still many do not enter into marriage agreements. In October 2016 the Constitutional Court gave decision No. 69 / PUU / XIII / 2015 made a shift in the meaning and norms related to the marriage agreement which impacted the joint assets for this study entitled "Juridical Implications of Constitutional Court Decree No.69 / PUU / XIII / 2015 Concerning Marriage Agreements on Joint Property for Mixed Marriage "The method used is normative literature with an interesting type of legal principle to get a comprehensive picture of the problems under study and analyze existing literature to obtain information as an academic text as a consideration for making rules regarding problems that arise. Referring to the decision of the Constitutional Court, the marriage agreement is no longer carried out before marriage but can also be done during the marriage, so it is interesting to examine how the background relates to the decision and how the joint property in mixed marriages follows the decision of the Constitutional Court. Key Work : Mixed Marriages, Marriage Agreement, Shared Assets.